A flexible solid-state supercapacitor with extreme low-temperature tolerance based on an ion conducting ice gel electrolyte. Issue 13 (23rd February 2022) - Tu, Juan.; Pan, Jian; Liu, Xinghuan; Yan, Yinhao; Shi, Yulin; Yu, Xinghai; Jia, Xin
Abstract : An innovative ion conducting ice gel served as a solid-state electrolyte in a flexible supercapacitor with improved extreme low-temperature tolerance. Abstract : Enhancing the low-temperature tolerance of electrochemical energy storage devices ( e.g. supercapacitors, rechargeable batteries) in a cold climate is important for automobiles, wearable devices, and smart grids used in high-altitude areas and polar regions. Recently, supercapacitors' longevity and performance under varied temperature conditions, especially low temperature, have received widespread attention. However, until now, the sluggish ion diffusion caused by electrolyte freezing restricts the low-temperature performance and durability of supercapacitors. Herein, an innovative solid-state ion conducting ice gel (IG) with a high conductivity (1.79 × 10 −4 S cm −1 at −15 °C), favorable flexibility, and significant low-temperature tolerance was designed and prepared by compositing polyvinyl alcohol (PVA) and CuSO4 ·5H2 O salt through ultra-fast liquid nitrogen freezing. Thereafter, a symmetrical configuration supercapacitor was assembled with two flexible electrodes and IG electrolytes. The IG electrolytes feature a distinct solid-state ion conductor that can provide efficient ion transportability to the supercapacitor at extremely cold temperatures with remarkable electrochemical performances. For example, even at −80 °C, the supercapacitor performed well with a capacitance retention rate of 91.8% after 7000 cycles. Besides, the remarkable mechanical properties derived from the IG electrolytes also endow the supercapacitor with great durability under various harsh deformations in sub-zero surroundings. This work will open up a new avenue for developing versatile solid–gel electrolytes with broad working temperature ranges under harsh conditions for portable and wearable energy storage devices.